Gambaran Tingkat Pengetahuan Dan Sikap Pemuda Tentang Kesiapsiagaan Bencana Tanah Longsor Di Desa Ngargoyoso - Fitriana; Fida’ Husain (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Background: Referring to the data released by the International Disaster Database in 2018, 315 natural disaster events were recorded. According to the NDMA (National Disaster Management Authority), there have been 309 landslide disasters recorded in Indonesia. Furthermore, the LADC (Local Agency for Disaster Countermeasure) of Karanganyar district recorded 50 landslides in 2020 in Ngargoyoso District. The lack of knowledge and attitudes regarding landslide disaster preparedness caused a significant disaster risk. Aim: To discover the knowledge level and the attitudes of the youths in Ngargoyoso regarding landslide preparedness. Method: This research was descriptive by using a purposive sampling technique with the number of sampling was 58 youths in Melikan village, along with the youth’s inclusion criteria which are willing to be respondents, actively participate in the youth organization, as well as the youths aged from 10-24 year old. Result: The univariate results exposed the respondent’s characteristics in which some of the youths are with senior high school education (63.8%), male gender (51.7%), unemployed (58.6%), youth’s knowledge levels in high category (50.0%) and youth attitudes in the high category (41.6%). Conclusion: This study showed that the level of youth’s knowledge and attitudes in Ngargoyoso village about preparedness is high.